Can a reresection be avoided after initial en bloc resection for high-risk nonmuscle invasive bladder cancer? A systematic review and meta-analysis - Xu, Jiangnan; Xu, Zhenyu; Yin, HuMin; Zang, Jin (Frontiers in Surgery, 2022)
Background: To evaluate the effectiveness of en bloc resection for patients with non-muscle invasive bladder cancer (NMIBC) and explore whether a reresection be avoided after initial en bloc resection. Material and Methods: A research was conducted in PubMed, EMBASE, Cochrane Library and Web of Science up to October 12, 2021 to identify studies on second resection after initial en bloc resection of bladder tumor (ERBT). R software and double arcsine method were used for data conversion and combined calculation of incidence rate. Results: A total of 8 studies involving 414 participants were included. The rate of detrusor muscle in the ERBT specimens was 100% (95%CI:100%-100%), the rate of tumor residual in reresection specimens was 3.2% (95%CI:1.4%-5.5%), the rate of tumor upstaging was 0.3% (95%CI:0%-1.5%). Two articles compared the prognostic data of reresection and non-reresection group after the initial ERBT. We found no significant difference in 1-year recurrence-free survival (RFS) rate (OR=1.44, 95%CI 0.67 to 3.09, P=0.35) between the two groups, nor in the rate of tumor recurrence (OR=0.72, 95%CI 0.44 to 1.18, P=0.2) or progression (OR=0.98, 95%CI 0.33 to 2.89, P=0.97) at final follow-up. Conclusions: ERBT can almost completely remove the detrusor muscle of the tumor bed with very low postoperative tumor residue and upstaging rate. For high-risk NMIBC patients, reresection after ERBT did not appear to improve prognosis, and its use can be appropriately reduced.